WITOLD GOMBROWICZʼS DIARY. EXILE AS MODUS VIVENDI - Sofinkić, Milica (Philological Studies, 2023)
This paper examines autobiographical writing in the context of modern theories and research, using Witold Gombrowiczʼs Diary as an example. Specifically, it analyzes the degree to which the Diary leans towards autofiction, or the fusion of autobiography and fiction, and the extent to which it remains rooted in reality. Gombrowiczʼs Diary covers the period between 1953 and 1966, and is characterized by a mixture of self-reflection and autopoetics. Although the author draws from his own experiences and real events, he also explores the limits of the diary as a literary genre by fictionalizing it. While Gombrowiczʼs use of the diary form places him within the tradition of autobiographical discourse, his thematic focus on the experience of exile aligns him with the literature of exile. Through his Diary, Gombrowicz seeks to articulate the fundamental existential state of being in exile during a specific period of his life. The aim of this paper is to examine the concept of otherness in Gombrowicz’s magnum opus, respecting the authorʼs determination to communicate his experience in a formally non-literary text. In doing so, several questions are raised: Is the narrator of the autobiographical prose identical to the author? To what extent does literariness feature in the text, as compared to the presence of an aesthetic component in the sense of Russian Formalism? How is the supposed binary opposition of domestic and foreign reconciled?